Razvoj prometnic v območju mednarodnega mejnega prehoda Vrtojba - Juvanc, Alojzij (Urbani izziv, 2005)
The Republic of Slovenia is part of the European Union. With the abolishment of borders (free flow of goods) also the traffic functions in the areas of international border crossings between member countries are changing. Among such border crossings is also the international border crossing (IBC) between the Republic of Italy and the Republic of Slovenia in Vrtojba. The bordering communities of Šempeter-Vrtojba and Gorizia (Italy) are therefore already preparing a development plan related to the use of space to ensure traffic access to the wider area of this border crossing ,when the "Schengen border" is abolished (free flow of people). Especially important is adequate design ofroads that should allow this space to be uniformly and equally included intothe road systems of both neighboring countries. Owing to this change, the existing "communal" road, which today leads to the border crossing, will attain the status of the expressway Ljubljana-Venice via Gorizia, which means that high traveling speeds and changed regime of connecting roads can be expected. The existing arrangement has too many individual connections, and there is the possibility of turning or even parking (in Italy). The paper presents solutions or proposals for a systematic rearrangement of the present road through the IBC to the motorway and the principle of connecting the road networks of both neighboring communities to it. Presented are also proposals how to rearrange or complete the existing local road networks and the railway infrastructure (arrangement of an intermodal terminal), and the traffic regimeon roads to achieve as efficient use of space as possible at the presentIBC Vrtojba with the least possible burden to the space.
Keywords: ceste; cestno omrežje; državne meje; mejni prehodi; obmejna območja; prostorsko planiranje; spatial planning